Improving French bean yield potential through induced mutagenesis using EMS and SA - Laskar, Rafiul Amin; Dowarah, Bhaskar; Tamang, Dilip; Das, Sangeeta; Borah, Protiva; Raina, Aamir (Frontiers in Horticulture, 2024)
Introduction French bean (Phaseolus vulgaris L.) holds global significance as one of the most consumed legumes, with commercial value surpassing that of all other legume crops combined. In India, the consumption of French beans has grown steadily, especially in the North Eastern region, driven by heightened consumer interest in its nutritional benefits. Considering these factors, we initiated an induced mutagenesis program to enhance the genetic diversity of locally grown French bean genotypes, traditionally cultivated for their superior adaptability. Methods To achieve this, we initiated an induced mutagenesis program. Seeds from the village seed stock were subjected to treatments with varying doses of ethyl methane sulfonate (EMS) ranging from 0.1% to 0.4% and sodium azide (SA) from 0.1% to 0.4%. The objective was to increase yield potential and enhance genetic diversity. Results The treatment with EMS and SA led to a non-specific, dosage-independent reduction in biophysiological characteristics in French bean mutants. Notably, the 0.4% SA treatment significantly inhibited germination and fertility, causing a decrease in chlorophyll (10.02 mg. g-1 FW) and carotenoid (1.57 mg. g-1 FW) levels. This suggests a disruption in genes associated with chlorophyll and carotenoid synthesis. However, in the M2 generation, the mutagenic treatments substantially improved yield and associated traits. The highest pod yield per plant was recorded at 79.50 gm for the 0.2% EMS treatment. A character association study revealed strong correlations (0.217 to 0.995) between pod yield and other agronomic traits. Discussion The results indicate that selecting mutants based on these traits in populations treated with EMS and SA can significantly increase crop yield. The 0.2% SA and 0.2% EMS M2 mutant populations exhibited the highest induced variability, making them ideal for selecting higher-yielding mutant lines for further breeding generations. The increased yields in these mutant lines, derived from a local cultivar, show promise for meeting the growing demand for French bean production through their widespread cultivation.